2010
DOI: 10.1093/intimm/dxq025
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine expression in renal ischemia/reperfusion injury is most profound during the reparative phase

Abstract: Chemokines are important players in the migration of leukocytes to sites of injury and are also involved in angiogenesis, development and wound healing. In this study, we performed microarray analyses to identify chemokines that play a role during the inflammatory and repair phase after renal ischemia/reperfusion (I/R) injury and investigated the temporal relationship between chemokine expression, leukocyte accumulation and renal damage/repair. C57Bl/6 mice were subjected to unilateral ischemia for 45 min and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 46 publications
2
67
1
5
Order By: Relevance
“…One day after reperfusion, the time point at which neutrophil influx peaks, 5 chimeric mice in which leukocytes were Nlrp3 deficient did not show reduced renal damage 15 and function (this study). Therefore, we speculated that Nlrp3 in macrophages, of which influx peaks at day 5, 10 rather than neutrophils is important for differences in renal damage in the late phase of renal IR injury.…”
Section: Nlrp3 Regulates Renal Repairmentioning
confidence: 52%
See 1 more Smart Citation
“…One day after reperfusion, the time point at which neutrophil influx peaks, 5 chimeric mice in which leukocytes were Nlrp3 deficient did not show reduced renal damage 15 and function (this study). Therefore, we speculated that Nlrp3 in macrophages, of which influx peaks at day 5, 10 rather than neutrophils is important for differences in renal damage in the late phase of renal IR injury.…”
Section: Nlrp3 Regulates Renal Repairmentioning
confidence: 52%
“…2 After injury, wounded tissue organizes an efficient response that aims to combat infections, clear cell debris, re-establish cell number, and reorganize tissue architecture. First, necrotic tissue releases dangerassociated molecular patterns, such as high-mobility group box-1 3 or mitochondrial DNA, 4 which leads to chemokine secretion 5 and a subsequent influx of leukocytes. Second, neutrophils and macrophages clear cellular debris but also increase renal damage because depletion of neutrophils 6 or macrophages within 48 hours of IR will reduce renal damage.…”
mentioning
confidence: 99%
“…MIP-2 is expressed in the kidney (31), and induced with injury (22,36,40), but its specific tubular localization has not been well-defined. The role of MIP-2 in the recruitment of neutrophils after kidney injury has been previously studied by Miura and colleagues (23), where neutralization of MIP-2 by specific antibodies in a mouse model of ischemia-reperfusion reduced neutrophil infiltration and attenuated kidney injury (23).…”
Section: Discussionmentioning
confidence: 99%
“…This chemokine is thought to play an important role in neutrophil recruitment to the site of injury during AKI (22,23,40). Although MIP-2 expression is induced after ischemiareperfusion (36), its specific tubular localization has not been well-defined in the context of AKI.…”
mentioning
confidence: 99%
“…Animal experiment and clinical observations have indicated that under the conditions of ischemia, hypoxia, intoxication, inflammation, and allergic reaction, expression of MCP-1 is elevated. 7,8 MCP-1/CCR2 signaling contributes to the pathogenesis of renal I/R injury, 9 and blockage of the signaling rescues renal I/R injury. 10 In rat renal I/R injury, cytokine KC and MIP-2 are also upregulated.…”
Section: Introductionmentioning
confidence: 99%